Identification of Secondary Metabolite Compounds in Two Varieties of Young Winged Beans (Psophocarpus tetragonolobus L.) at Two Harvest Ages - Susanti, Destia; Melati, Maya; Kurniawati, Ani (Department of Agronomy and Horticulture, IPB University, 2022)
The winged bean (Psophocarpus tetragonolobus L.) is a member of the Fabaceae family (beans). Winged bean is developed as a vegetable, and young winged bean pods can be consumed fresh, steamed, fried, or pickled. In Southeast Asia, winged bean pods are generally cooked or consumed as side dishes or salad. Winged bean contains high protein content equivalent to soybean seed. Besides being rich in protein, vitamins, and minerals, the winged bean also has secondary metabolites, including phenolics and flavonoids. This study aimed to identify secondary metabolites in young pods of two varieties, “Fairuz” and “Sandi”, at two different harvest ages of 8 and 10 days after anthesis (DAA) and provide the biological activity on each identified compound. The experiment was conducted at the IPB experimental field at Leuwikopo, Bogor, from September 2020 to February 2021. The identification of secondary metabolites of the young green pods “Fairuz”, and the young purple pods “Sandi”, was performed using the GCMS method at the Regional Health Laboratory (KESDA) DKI Jakarta. The results of the GCMS analysis showed that 1,2-enzenedicarboxylic acid, mono(2-Ethylhexyl) ester was the most abundant compound identified from pods harvested at 8 DAA in both varieties, namely 42.26% in “Fairuz” and 26.66% in “Sandi”. Other compounds, 9,12,15-Octadecatrienoic acid, ethyl ester, (Z, Z, Z) (Linoleic acid ester), were found in “Fairuz”, whereas (9E,12E)-9,12-Octadecadienoic acid (Linoleic acid) was found in “Sandi”; these compounds are hydroxyl group and phenolic glucoside compounds and are found in pods harvested at 10 DAA.